Strategi Pengembangan Agroindustri Mengkudu di Kabupaten Jember - Setiawan, Andika Putra; Wardhana, Danu Indra; Nalawati, Ara Nugrahayu; Rismawati, Rizki (Fakultas Teknologi Pertanian Universitas Jember, 2026)
Jember Regency is one of the largest noni-producing regions in East Java Province. However, the development of noni agroindustry has not yet reached its full potential. Various constraints related to raw material management, processing technology, business capital, and market access have limited the growth and competitiveness of the sector. This study was conducted in Jember Regency, East Java, Indonesia, to formulate an appropriate strategy for developing the noni agroindustry. The research employed the Hayami method to analyze value added, the Exponential Comparison Method to determine superior agroindustrial products, Interpretative Structural Modeling to identify key development elements, and the Analytical Hierarchy Process to prioritize development strategies. The results showed that processing 336,000 kg of noni fruit generated 168,000 L of liquid extract, 56,000 kg of chips, and 16,800 kg of noni coffee. Among the evaluated products, noni extract beverage was identified as the most prospective product for agroindustrial development. The key development elements included creating business opportunities for micro, small, and medium enterprises, strengthening processing technology from upstream to downstream, overcoming capital constraints, enhancing the role of buyers, and intensifying extension and promotional activities through conventional and digital channels. The priority strategy identified was improving market access, with a priority value of 0.254. The findings contribute to the development of a sustainable noni agroindustry model by integrating value-added enhancement, institutional strengthening, technological improvement, and market-oriented strategies. Practically, the results can serve as a reference for local governments, agroindustry actors, and stakeholders in designing policies and programs to increase the competitiveness of noni-based products, expand employment opportunities, strengthen rural enterprises, and support regional economic development in Jember Regency. Keywords: development strategy, market access, noni agroindustry, rural agroindustry